Analisis Metode Ceramah pada Pengajaran Pendidikan Agama Islam di Sekolah Dasar Negeri 15 Pematang Panjang Kecamatan Sijunjung Kabupaten Sijunjung - Utama, Rildwiani Putri (Medan Resource Center, 2023)
Pematang Panjang State Elementary School 15, situated in Sijunjung District, Sijunjung Regency, employs the lecture method in the teaching of Islamic Religious Education. In this subject, teachers frequently use the lecture method, where students primarily listen to the teacher during the learning process. However, teachers also integrate the lecture method with other learning approaches, such as discussions and question-and-answer sessions. This research was conducted at Pematang Panjang State Elementary School 15, focusing on the Islamic Religious Education subject. Despite the prevalent use of the lecture method, teachers combine it with other learning methods, including discussions and question-and-answer sessions. The findings reveal that the lecture method effectively enlivens the classroom atmosphere, increases interest in learning, and improves student learning outcomes at State Elementary School 15 Pematang Panjang, Sijunjung District, Sijunjung Regency.